Overcoming energy divergence with high-order and directional OAM pencil beams - Zhao, Yufei (2025)
This paper presents a novel approach to overcoming energy divergence in wireless communications using high-order and directional Orbital Angular Momentum (OAM) pencil beams. Traditional OAM beams, with their hollow intensity profiles, suffer significant energy dispersion over long distances. To address this, we introduce an innovative OAM transmitter design that generates directional OAM pencil beams without a central energy void, aligning with conventional planar wave antennas' radiation patterns while maintaining OAM wavefront phase variations. Key contributions include a new theory for OAM pencil beams, a method for generating these beams using leaky wave antennas, and an annular cavity waveguide slot antenna for higher-order OAM modes with a compact design. Simulation and test results show that the proposed OAM pencil beams not only exhibit high directional radiation characteristics but also easily achieve higher-order OAM topological modes, providing valuable insights for future advanced communication and detection systems based on OAM waves.